Comparative Analysis of Enterprise Architecture Frameworks Using TOGAF ADM and SPBE Architecture Based on Presidential Regulation No. 132 of 2022 - Panji Ramadhan Yudha Putra Hadjarati; Agung Mulyo Widodo; Budi Tjahjono (Green Publisher Indonesia, 2025)
This research aims to conduct a comparative analysis between two enterprise architecture frameworks: TOGAF ADM and Electronic-Based Government System Architecture (SPBE) based on Presidential Regulation No. 132 of 2022. TOGAF ADM is a framework commonly used in various types of organizations in the private and public sectors, while the SPBE Architecture is specifically designed for the Indonesian government sector. Through a qualitative descriptive approach, this study analyzes the principles, concepts, processes, and guidelines underlying each framework. This research is expected to provide insight for policy makers and enterprise architecture practitioners in choosing and implementing the framework that best suits the context and needs of their organization. In addition, this study also provides recommendations to improve the efficiency and effectiveness of implementing enterprise architecture in the public and private sectors in Indonesia. As well as its contribution to the efficiency and quality of government services. This research reviews the challenges in implementing the Electronic-Based Government System (SPBE) in Indonesian government institutions and proposes a solution by comparing TOGAF ADM and SPBE Architecture based on Presidential Regulation No. 132 of 2022. The motivation for this study is to improve the effectiveness and efficiency of SPBE implementation by selecting the most suitable framework. The method used involves analyzing structure, flexibility, technology integration, regulatory compliance, practical implementation, performance, and case studies. The results show that the implementation of TOGAF ADM and SPBE Architecture has their respective strengths and weaknesses, but a combination of both can achieve better outcomes in enhancing government performance and efficiency.